ANALISIS KLASIFIKASI TANAH DENGAN METODE UNIFIED SOIL CLASSIFICATION SYSTEM (USCS) (Studi Kasus : Wih Pesam - Bener Meriah) - Mustaqim; Ammar Fadhil; Fitri Muliani (Jurnal Rekayasa Teknik dan Teknologi, 2026)
This study aims to classify soil in Wih Pesam District, Bener Meriah Regency, using the Unified Soil Classification System (USCS). Soil classification is essential for construction planning as it affects stability and bearing capacity. Samples were collected from four villages-Kebun Baru, Wih Pesam, Wonosobo, and Pante Raya-with three points in each location. Laboratory tests included water content, Atterberg limits, grain size distribution, and bulk density. The results showed an average water content of 61.5%, liquid limit of 33.95%, plastic limit of 55.01%, grain gradation of 21.85%, and bulk density of 1.46. All samples were identified as coarse-grained soils dominated by sand, with more than 50% retained on the No. 200 sieve. Based on grain size analysis and coefficients (Cu and Cc), the soil is classified as poorly graded sand (SP). These findings provide local soil data that can support infrastructure design in the study area